AN ECONOMETRIC INVESTIGATION ON THE IMPACT OF ICT IN THE BUSINESS PROCESSES OF FINANCIAL INSTITUTIONS IN THE DEVELOPING COUNTRIES (International Journal of Engineering and Computer Science, 2013)
This paper presents Information and Communication Technology (ICT) as a strategic driver in the business processes of the financial institutions in Nigeria. Soundness of banks is important for the economic development of any country. In this work, an attempt was made to empirically examine the impact of key metric such as Infrastructure (ICT infrastructure), Intellectual Capital, IT Governance, ICT Service Management (ISM) Strategic Policy Framework (SPF) and Service Innovation on the business processes of the banks in Nigeria. The study was conducted with ten banks in Nigeria. The empirical results show that with the developments of the aforementioned key metrics, the soundness of the financial institutions both on microeconomics and macroeconomics scales will be enhanced. It was observed that with well developed financial institutions via ICT, the soundness of the banks will address the issues of good quality of service, good integrity system, cost reduction and profit maximization. A bivariate data model was developed through linear regression to ascertain the extent of correlation between ICT key indices and the attendant social economic index. [Keywords: ICT, Business, Process, Infrastructure, Bivariate, Model, Correlation, Indice